Essay on Bernard Stiegler’s history of mnemotechnics - B. V. Podoroga (Омский научный вестник: Серия "Общество. История. Современность", 2020)
The purpose of this article is to present history of memory techniques as it described by French philosopher Bernard Stiegler. It is shown that Stiegler speaks from the point of view of humanistic marxism arguing that the positive development of mnemotechnics is determined by their integration into symbolic relations, outside of which they becomes a means of consumer capitalism. History of mnemotechnics is divided on two large periods — preindustrial and industrial, where the former is determined by the dominance of religion, politics and culture, and the latter — by the law of surplus value. It is analyzed Stiegler’s understanding of mnemotechnics as «epiphylogenesis» or «third memory». The main features of mnemotechnical evolution, from the first inscriptions on stone tools to today’s global digital retentional apparatus, is reviewed